2016
DOI: 10.1021/acsbiomaterials.6b00238
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Peptide Nanofibers Improve Wound Healing in STZ-Induced Diabetic Rats

Abstract: Low expressions of angiogenic growth factors delay the healing of diabetic wounds by interfering with the process of blood vessel formation. Heparin mimetic peptide nanofibers can bind to and enhance production and activity of major angiogenic growth factors, including VEGF. In this study, we showed that heparin mimetic peptide nanofibers can serve as angiogenic scaffolds that allow slow release of growth factors and protect them from degradation, providing a new therapeutic way to accelerate healing of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…These findings motivated Senturk et al to test the ability of hmPA-based gels to heal diabetic wounds, in streptozotocin-induced diabetic mice; results confirmed the bioactive gels to have a key role in both inflammation and proliferation phases of wound-healing, by promoting angiogenesis, re-epithelialization and inflammatory response [ 77 ].…”
Section: Tissue Regeneration Peptidesmentioning
confidence: 91%
“…These findings motivated Senturk et al to test the ability of hmPA-based gels to heal diabetic wounds, in streptozotocin-induced diabetic mice; results confirmed the bioactive gels to have a key role in both inflammation and proliferation phases of wound-healing, by promoting angiogenesis, re-epithelialization and inflammatory response [ 77 ].…”
Section: Tissue Regeneration Peptidesmentioning
confidence: 91%
“… [ 80 ] Heparin mimetic peptide amphiphiles Nanofibers Enhance production and activity of major angiogenic growth factors (VEGF). [ 84 ] DMOG PCL fiber meshes Reducing the expression of pro-inflammatory factors (IL-1β,IL-6, and TNF-α), increasing anti-inflammatory factors (TGF-β1 and IL-4) and GFs (IGF-1, HB-EGF, NGF, and bFGF), and promoting angiogenesis (CD-31 and VEGF-α). [ 86 ] K 2 (SL) 6 K 2 MDP hydrogels Allowing rapid cellular infiltration, and thus are ideal for tissue engineering strategies.…”
Section: Substances Applied In Diabetic Wound Healingmentioning
confidence: 99%
“…Diabetic wounds usually suffer from an impaired wound healing process owing to the vascular impairment resulting from the delayed secretion of pro-angiogenic factors as well as reduced proliferation and migration of ECs and tissue re-epithelialization [255][256][257][258]. In this regard, many researchers have made significant attempts to develop an efficient pro-angiogenic wound dressing for accelerating diabetic wound healing and tackling this important societal and clinical challenge [133,259]. In 2018, Ren et al reported the successful fabrication of electrospun fibrous membranes made of poly(L-lactic acid) (PLLA) containing dimethyloxalylglycine (DMOG)-loaded mesoporous silica nanoparticles (DS) for potential usage in diabetic wound healing [260].…”
Section: Angiogenic Nanofibrous Mats For Skin Regenerationmentioning
confidence: 99%